Analysis of Water-Soluble Polysaccharides in an Edible Medicinal Plant Epimedium: Method Development, Validation, and Application. (27th November 2019) - Zhang, Hua-Feng; Niu, Li-Li; Yang, Xiao-Hua; Li, Lu
Abstract: Water-soluble polysaccharides are important constituents with evident health benefits in Epimedium . The aim of this study was to establish a specific, accurate, reproducible, and sensitive phenol-sulfuric acid method for the quantitative assay of Epimedium polysaccharides and to determine polysaccharides in Epimedium samples from Chinese markets. Galactose was adopted as the standard monosaccharide, and 486 nm was chosen as the detection wavelength. The optimal conditions for the color reaction were obtained using single factor experiments and an orthogonal test: temperature, 20°C; amount of 5% phenol, 0.3 mL; amount of concentrated sulfuric acid, 3.5 mL; incubation time, 20 min; and addition sequence, phenol-sample-sulfuric acid. The colored sample solution after chromogenic reaction exhibited high stability within 2 h. The calibration curve was linear within the range 5.00–60.00 μg/mL, and the correlation coefficient of the regression equation was 0.999. LOD and LOQ were 1.65 and 5.00 μg/mL, respectively. Recovery, intraday precision, interday precision, and accuracy were 97.43 to 103.80%, 0.73 to 3.48%, 1.21 to 2.75%, and 97.74 to 101.62%, respectively. Polysaccharides in 26 samples of Epimedium collected from different provinces of China were quantified by the proposed colorimetric method, and a large variation of contents of polysaccharides was observed among these samples.